1,3-Bis(4-bromophenyl)imidazolium chloride dihydrate - Garden, S.J.; Gama, P.E.; Tiekink, E.R.T.; Wardell, J.L.; Wardell, S.M.S.V.; Howie, R.A. (International Union of Crystallography, 2010)
In the title hydrated salt, C(15)H(11)Br(2)N(2)(+)center dot Cl(-)center dot 2H(2)O, the complete imidazolium cation is generated by a crystallographic twofold axis, with one C atom lying on the axis. The chloride ion and both water molecules of crystallization also lie on a crystallographic twofold axis of symmetry. The cation is non-planar, the dihedral angle formed between the central imidazolium and benzene rings being 12.9 (3)degrees; the dihedral angle between the symmetry-related benzene rings is 25.60 (13)degrees. In the crystal, O-H center dot center dot center dot Cl hydrogen bonds result in supramolecular chains along c mediated by eight-membered {center dot center dot center dot HOH center dot center dot center dot Cl}2 synthons. These are consolidated by C-H center dot center dot center dot O and pi-pi [centroid-centroid distance = 3.687 (3)angstrom] interactions.